SMU will officially launch SMU-X curriculum in academic year 2015-16 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2015)
SMU-X Initiative aims to bring about a mindset change through innovative curriculum and unconventional learning facilities. After three-and-a-half years of study and conceptualisation, Singapore Management University (SMU) will launch its new SMU-X Initiative in the forthcoming Academic Year (AY) 2015-16, which begins in August. Key to this milestone is the introduction of a suite of new SMU-X courses following a six-month pilot. The University, which celebrates its 15th anniversary this year, is known for doing things differently. Besides offering an American style of education done in small, interactive seminar groups, it is also the first to introduce compulsory community service and internship, as well as broader admission criteria. The SMU-X Initiative, a paradigm shift which focuses on learning (as opposed to teaching), contributes towards the University’s 2025 vision of being a leader in transformative education, and reflects SMU’s commitment to stay ahead of innovative pedagogy by pushing the boundaries and venturing into new ways of bridging theory and practice.